1941 (pre-war half-year period): changes in the NKVD structure of the Ukrainian Soviet Socialist Republic - V. A. Grechenko (Bulletin of Kharkiv National University of Internal Affairs)
1941 is a landmark in the history of the world in the whole and Ukraine in particular. The absolute attention of the historical scientific community is concentrated on the events associated with the beginning of the Soviet-German war. Therefore, a very small number of publications is focused on the pre-war half-year period of 1941. However, the reorganization of the NKVD continued during this period aiming at adapting its activities to new tasks. The study of controversial pages of law enforcement agencies at this time is important for the reproduction of an objective picture of its activity, for the establishment of historical truth. The author of the publication has studied the transformations in the structure of the NKVD of the Ukrainian Soviet Socialist Republic during the first pre-war half-year period of 1941.